Associative connections of stimuli PEACE and WAR: semantic content (on the material of a chain associative experiment with humanities students) - Васянович, Євгенія Андріївна; Дубовик, Наталія Миколаївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2021)
The paper is devoted to the study of the associative relations of the lexemes PEACE and WAR. The aim of the work is to reveal the cultural component of the associative fields of the stimulus words PEACE and WAR. Due to the object of study (the associative connections of stimuli PEACE and WAR in the linguistic consciousness of humanities students) we consider the usage of associative psycholinguistic experiment to be the most appropriate, because the object cannot be observed directly. The paper outlines the methodological grounds for such study. The material for the article was the associative reactions obtained during the experiment with humanities students. On the basis of the received data the quantitative, mathematical and qualitative analyses of semantic content of associative fields of stimuli PEACE and WAR are realized. The analysis showed that the mutual influence of culture and language is reflected in the associative content of these stimuli, and hence in the linguistic consciousness in which such connections are contained. It is concluded that students receive certain cultural codes from the experience of their nation through language, as they are embodied in language signs. This fact demonstrates that a person is both an object and a subject of culture. The obtained reactions suggest that linguistic culture has greater impact on associative connections than individual, personal experience. It is impossible to deny the influence of ethnic factors on the worldview and the formation of consciousness of a particular linguistic and cultural community. The PEACE and WAR associations presents an inseparable connection between them in the linguistic and cultural consciousness of humanities students and they can exist only in opposition to each other.